Experience of severe desaturation during anesthetic induction period in an obese adult patient with Prader-Willi syndrome -A case report- - Joon Woo Choi (Korean Journal of Anesthesiology, 2012)
Prader-Willi syndrome is characterized by infantile hypotonia, childhood-onset obesity, short stature, mental retardation, hyperphagia, hypogonadism. After infantile hypotonia phase, patient is prone to morbid obesity due to hyperphagia. Complications associated with morbid obesity are recognized as the main risk factors for death the lifespan of patients with Prader-Willi syndrome. We experienced desaturation and bronchospasm during arteriovenous fistula surgery in an obese adult with Prader-Willi syndrome.